Tolerating the “doubting Thomas”: how centrality of religious beliefs vs. practices influences prejudice against atheists - Hughes, Jeffrey; Grossmann, Igor; Cohen, Adam B. (Frontiers in Psychology, 2015)
Past research has found a robust effect of prejudice against atheists in largely Christian-dominated (belief-oriented) samples. We propose that religious centrality of beliefs vs. practices influences attitudes toward atheists, such that religious groups emphasizing beliefs perceive non-believers more negatively than believers, while groups emphasizing practices perceive non-practicing individuals more negatively than practicing individuals. Studies 1-2, in surveys of 41 countries, found that Muslims and Protestants (belief-oriented) had more negative attitudes toward atheists than did Jews and Hindus (practice-oriented). Study 3 experimentally manipulated a target individual’s beliefs and practices. Protestants had more negative attitudes toward a non-believer (vs. a believer), whereas Jews had more negative attitudes toward a non-practicing individual (vs. a practicing individual, particularly when they had a Jewish background). This research has implications for the psychology of religion, anti-atheist prejudice, and cross-cultural attitudes regarding where dissent in beliefs or practices may be tolerated or censured within religious groups.